TOLERANCE AS A PRIME VIRTUE OF HUMANITY (World Bulletin of Social Sciences, 2023)
A person’s place in society and, naturally, is not limited to the expression of his own nationality, ethno-spiritual and racial characteristics. In this case, a person should not deny other aspects of social existence. At the same time, in the scientific literature, there are also cases of overstating the specific nationality and national aspects reflected in a person’s personality. This naturally leads to the denigration of other people’s national dignity